2021
DOI: 10.1177/20563051211055439
|View full text |Cite
|
Sign up to set email alerts
|

What Will They Think If I Post This? Risks and Returns for Political Expression Across Platforms

Abstract: Social networking sites (SNSs) allow individuals to establish and maintain a variety of relationships as well as share different aspects of their identity by expressing their views on numerous topics, including politics. SNS also come with perceived interpersonal risks and benefits tied to sharing with a collapsed networked audience. Using a nationally representative sample of US social media users ( N = 2,873) from 2016, this study investigated how perceived network characteristics influence people’s decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Research should look further into the perceptions of, and practices in, social media by people that have grown up with offline/online entangled public spheres. The extent to which space attentiveness and protective strategies are connected to people's specific age, generational status (Fang et al, 2019), and/or life situation (Parviz & Piercy, 2021), or whether it becomes increasingly prevalent across generations as the amount of people accustomed to profit-seeking social media grows, should be further scrutinized. If the latter would turn out true, Tim Hwang's (2020) call for policies (due to an "attention crisis") may have relevance beyond online advertising systems and the status of its continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Research should look further into the perceptions of, and practices in, social media by people that have grown up with offline/online entangled public spheres. The extent to which space attentiveness and protective strategies are connected to people's specific age, generational status (Fang et al, 2019), and/or life situation (Parviz & Piercy, 2021), or whether it becomes increasingly prevalent across generations as the amount of people accustomed to profit-seeking social media grows, should be further scrutinized. If the latter would turn out true, Tim Hwang's (2020) call for policies (due to an "attention crisis") may have relevance beyond online advertising systems and the status of its continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that social media not only afford new tools for political communication (Bode et al, 2014; Theocharis & van Deth, 2018) but as spaces where political communication unfolds, they also enable processes of social and communicative change (Flanagin, 2020). Specifically, social media alter the nature of engagement in the public life (Baym & boyd, 2012), including changes in citizenship norms, for example, due to risk-return calculations (Parviz & Piercy, 2021).…”
Section: Changing Participation Forms Changing Citizenship Normsmentioning
confidence: 99%
“…For example, norms can emerge due to individual or collective actions that harm or benefit individuals and collectives (Coleman, 1990; Opp, 2001). Although social media environments induce benefits for individuals’ civic participation (such as political mobilization on an unprecedented scale or political emancipation through self-expression), they also induce harmful experiences that may constrain individual agency (such as hate speech that aims to intimidate and discriminate) (Parviz & Piercy, 2021). In the presence of both harms and benefits, there is reason to believe that there would be a demand for norms (Coleman, 1990) that help people navigate social media environments in a democratic sense.…”
Section: Changing Participation Forms Changing Citizenship Normsmentioning
confidence: 99%
“…As social media have greatly expanded the opportunity for personal and political expression, research has attended to how people use platforms to these aims (O'Sullivan & Carr, 2018). In terms of opinion expression, this work has documented the role social media plays as a medium through which citizens can publicly express and discuss their beliefs on different topics and across different contexts (Parviz & Piercy, 2021).…”
mentioning
confidence: 99%
“…Yet research on social media opinion expression has tended to focus on sentiment (Ceron et al, 2014) rather than discrete emotions (Hasell & Weeks, 2016) and has generally focused on public expression (Parviz & Piercy, 2021; Waterloo et al, 2018). In this study, we extend prior work by empirically examining the differences between how people manage emotions when communicating publicly and privately.…”
mentioning
confidence: 99%